Guided Discovery Learning With Concept Hierarki, Can Improve Critical Thinking Ability and Student Learning Achievements - Assa'adah, Putri Alvy; Ashadi, Ashadi; Mulyani, Sri (Universitas Sebelas Maret, 2019)
The purpose of this study is to improve the critical thinking skill and students’ learning achievement of X grade MIPA 1 in the material of redox reaction in one of senior high school of Surakarta through the application of Guided Discovery learning models that assisted by concept of hierarchy. The type of this research was Classroom Action Research (CAR). Subjects of this research were X grade MIPA 1. The technique of collecting data were taken by observation, interviews, document, questionnaires, and tests. The data validity of this research was tested by using triangulation technique. The result of this research showed that guided discovery learning model was assisted by concept of hierarchy could improved critical thinking skill (65.63% in the first cycle to 100% in the second cycle) and students’ learning achievement (on knowledge aspect was 43.75% in the first cycle to 90.63% in the second cycle) in the material of redox reaction. While the aspect of attitude showed that there was improvement of percentage from 90.63% in the first cycle to 100% in the second cycle. Percentage of skill aspect was 100% in the first cycle.